Cocoa production and processing technology [ - Afoakwa, Emmanuel Ohene (CRC Press, 2014)
One of the largest food commodities exported from the developing countries to the rest of the world, cocoa has gained increasing attention on the global market - raising many questions about its quality, sustainability and traceability. Cocoa Production and Processing Technology presents detailed explanations of the technologies that could be employed to assure sustainable production of high-quality and safe cocoa beans for the global confectionary industry. It provides overviews of up-to-date technologies and approaches to modern cocoa production practices, global production and consumption trends as well as principles of cocoa processing and chocolate manufacture. The book covers the origin, history and taxonomy of cocoa, and examines the fairtrade and organic cocoa industries and their influence on smallholder farmers. The chapters provide in-depth coverage of cocoa cultivation, harvesting and post-harvest treatments with a focus on cocoa bean composition, genotypic variations and their influence on quality, post-harvest pre-treatments, fermentation techniques, drying, storage and transportation. The author provides details on cocoa fermentation processes as well as the biochemical and microbiological changes involved and how they influence flavour. He also addresses cocoa trading systems, bean selection and quality criteria, as well as industrial processing of fermented and dried cocoa beans into liquor, cake, butter and powder. The book examines the general principles of chocolate manufacture, detailing the various stages of the processes involved, the factors that influence the quality characteristics and strategies to avoid post-processing quality defects. This volume presents innovative techniques for sustainability and traceability in high-quality cocoa production and explores new product development with potential for cost reduction as well as improved cocoa bean and chocolate product quality